APLIKASI WIND POWERED COMPOSTER DI KAWASAN PESISIR KELURAHAN CAMBAYYA KOTA MAKASSAR - Ramdiana Ramdiana; Nani Anggraini; Sattar Yunus; Hadiratul Kudsiah (LP2M Universitas Hasanuddin, 2020)
Application of Wind Powered Composter in the Coastal Area of Cambayya Village, Makassar CityAbstract. Cambayya Village is one of the coastal areas of Makassar City which has a very complex waste condition, which is garbage from the people who live and carry out activities in the coastal area, garbage sent from land area that flows from rivers or gutters that flow into the coast. The Community Service Program aims to conduct activities in the form of training, practice and assistance in processing organic waste into compost using Wind Powered Composter technology located in the RT A community group of Cambayya Village. The problem by partners is the large amount of garbage generated in the coastal settlements of Cambayya Village, residents do not yet know how to process organic waste, and there is no practical application of renewable technology that is acceptable to the community in environmental management. The technology applied is Wind Powered Composter Technology which is an organic waste processing technology using wind power as an energy source to produce compost that can be useful for greening and economic value. This method is contained from a few stages: Preparation stage, namely processing permits, socializing activities to partners, and preparing training materials, Implementation stage conducting motivational training in processing waste, training on organic waste sorting, making composter equipment, making use of SOP training, the practice of composting, harvest compost and compost packaging, The evaluation stage by providing assistance and periodic checking of the composting process. The results of the implementation of this activity are the reduction in the volume of 60 kg of organic waste in each composting process, increased knowledge of citizens about organic waste processing, and the application of appropriate technology in coastal areas.Keywords: Organic waste, composter, wind poweredAbstrak. Kelurahan Cambayya merupakan salah satu wilayah pesisir Kota Makassar yang memiliki kondisi sampah yang sangat kompleks yaitu sampah dari masyarakat yang tinggal dan melakukan aktivitas di wilayah pesisir, sampah kiriman dari wilayah daratan atas yang mengalir dari sungai atau selokan yang bermuara ke pesisir. Adanya program Pengabdian kepada Masyarakat ini bertujuan melakukan kegiatan dalam bentuk pelatihan, praktek dan pendampingan dalam pengolahan sampah organik menjadi kompos dengan menggunakan teknologi Wind Powered Composter yang berlokasi di kelompok warga RT A Kelurahan Cambayya. Masalah yang dihadapi mitra adalah banyaknya timbulan sampah yang dihasilkan di permukiman pesisir Kelurahan Cambayya, warga belum mengetahui cara mengolah sampah organik, dan belum ada penerapan teknologi terbarukan yang praktis dan mampu diterima masyarakat dalam pengelolaan lingkungan. Teknologi yang diterapkan adalah Teknologi Wind Powered Composter yang merupakan teknologi pengolahan sampah organik menggunakan tenaga angin sebagai sumber energi menghasilkan kompos yang dapat bermanfaat untuk penghijauan dan bernilai ekonomi. Metode kegiatan ini diantaranya: Tahap persiapan yaitu pengurusan surat izin, sosialisasi kegiatan ke mitra, dan persiapan materi pelatihan, Tahap pelaksanaan melakukan pelatihan motivasi dalam mengolah sampah, pelatihan pemilahan sampah organik, pembuatan alat komposter, pelatihan SOP penggunaan alat, praktek pembuatan kompos, panen kompos, dan pengemasan kompos, Tahap evaluasi dengan melakukan pendampingan dan pengecekan berkala terhadap proses pembuatan kompos. Hasil pelaksanaan kegiatan ini adalah berkurangnya volume sampah organik maksimal 60 kg dalam setiap proses pengomposan, meningkatnya pengetahuan warga tentang pengolahan sampah organik, dan telah diterapkannya teknologi tepat guna di kawasan pesisir.Kata Kunci: Sampah organik, komposter, tenaga Angin